2018
DOI: 10.1080/13816810.2018.1432061
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between HDAC6, CXCR3, and SIRT1 genes expression levels with progression of primary open-angle glaucoma

Abstract: The expression level of HDAC6, CXCR3, and SIRT1 genes may be involved in the progression of POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The results of our studies show that HDAC6 inhibition by TS decreased the appearance of the senescence marker γH2AX and significantly augmented the expression of the redox homeostatic histone deacetylase SIRT1, of which expression levels are inversely correlated with the induction of endothelial cell senescence [4,7]. A contrasting balance between HDAC6 and SIRT1 could significantly impact the redox status of a number of cells including endothelial and other retinal cells [28].…”
Section: Discussionmentioning
confidence: 72%
“…The results of our studies show that HDAC6 inhibition by TS decreased the appearance of the senescence marker γH2AX and significantly augmented the expression of the redox homeostatic histone deacetylase SIRT1, of which expression levels are inversely correlated with the induction of endothelial cell senescence [4,7]. A contrasting balance between HDAC6 and SIRT1 could significantly impact the redox status of a number of cells including endothelial and other retinal cells [28].…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, it has been observed that there is an increase in cell-adhesion molecules on the endothelial cells in inflamed retinas. Moreover, RGCs have been reported to express many chemokines that are responsible for chemokine recruitment [60][61][62]. However, many aspects of immune infiltration and BRB integrity and their role in glaucoma pathogenesis remain elusive (Fig.…”
Section: Glial Cells Responses In Glaucoma: a Systematic Reviewmentioning
confidence: 99%
“…Another pair of chemokines (C-X-C motif) ligand 10/(C-X-C motif) receptor 3 (CXCL10/CXCR3) are found to be induced by acute IOP elevation and subsequently contribute to the release of proinflammatory cytokines, elevated expression of E-selectin, and infiltration of inflammatory cells ( 91 ). In patients with glaucoma, the levels of chemokines of macrophage chemoattractant protein-1 (MCP-1), CXCR3, CCL2, and CCL7 show prognostic value and are correlated with disease progression ( 92 94 ). On the other hand, the induced expression of corresponding chemokines and receptors on the T cell surface under inflamed conditions favors their interplay with the vascular endothelium ( 90 , 95 ).…”
Section: Compromised Brb Is Essential For T Cell Infiltration In Glaucoma Eyesmentioning
confidence: 99%